Reprint of – Deep-sea coral and hardbottom habitats on the west Florida slope, eastern Gulf of Mexico. (September 2017) - Ross, Steve W.; Rhode, Mike; Brooke, Sandra
Abstract: Until recently, benthic habitats dominated by deep-sea corals (DSC) appeared to be less extensive on the slope of the Gulf of Mexico (GOM) than in the northeast Atlantic Ocean or off the southeastern US. There are relatively few bioherms (i.e., coral-built mounds) in the northern GOM, and most DSCs are attached to existing hard substrata (e.g., authigenically formed carbonate). The primary structure-forming, DSC in the GOM is Lophelia pertusa, but structure is also provided by other living and dead scleractinians, antipatharians (black corals), octocorals (gorgonians, soft corals), hydrocorals and sponges, as well as abundant rocky substrata. The best development of DSCs in the GOM was previously documented within Viosca Knoll oil and gas lease blocks 826 and 862/906 (north-central GOM) and on the Campeche Bank (southern GOM in Mexican waters). This paper documents extensive deep reef ecosystems composed of DSC and rocky hard-bottom recently surveyed on the West Florida Slope (WFS, eastern GOM) during six research cruises (2008–2012). Using multibeam sonar, CTD casts, and video from underwater vehicles, we describe the physical and oceanographic characteristics of these deep reefs and provide size or area estimates of deep coral and hardground habitats. The multibeam sonar analyses revealed hundreds of mounds and ridges, some of which were subsequently surveyed using underwater vehicles. Mounds and ridges in <525 m depths were usually capped with living coral colonies, dominated by L . pertusa . An extensive rocky scarp, running roughly north-south for at least 229 km, supported lower abundances of scleractinian corals than the mounds and ridges, despite an abundance of settlement substrata. Areal comparisons suggested that the WFS may exceed other parts of the GOM slope in extent of living deep coral coverage and other deep-reef habitat (dead coral and rock). The complex WFS region warrants additional studies to better understand the influences of oceanography and geology on the occurrence of DSC and associated organisms. Protection measures are being considered to ensure the long-term integrity of this diverse ecosystem. Highlights: Extensive deep (~400–600 m) reef ecosystems were documented on the West Florida Slope, Gulf of Mexico. Multibeam mapping and video surveys revealed a rocky scarp running at least 229 km. Numerous mound and ledge complexes occurred west of the scarp. Living Lophelia pertusa colonies were abundant west of the scarp above 525 m depth. West Florida Slope may contain more complex reef habitat than elsewhere on the GOM slope.